2014
DOI: 10.7883/yoken.67.333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Detection Rates of RT-PCR and Virus Culture Using a Combination of Specimens from Multiple Sites for Enterovirus-Associated Encephalomyelitis during Enterovirus 71 Epidemic

Abstract: SUMMARY: Enterovirus (EV) 71 may cause severe neurological illness in the pediatric population. The present study aimed to compare the detection rates of reverse transcription-polymerase chain reaction (RT-PCR) with pan-EV/EV71 type-specific primers and virus culture (VC) for the identification of EV and EV71 using specimens from multiple sites. In total, specimens from throat/rectal swabs, cerebrospinal fluid (CSF), and blood from 66 patients diagnosed with EV encephalomyelitis were subjected to both RT-PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Although CSF testing is usually positive in enterovirus aseptic meningitis, it is frequently negative in EV71-associated neurological disease, including encephalomyelitis. 3,17,[38][39][40] The present study established that, despite high rates of CNS involvement, EV71 was infrequently identified from CSF specimens, while throat, stool, or rectal swabs had high diagnostic yields. Viral load in the CSF may be low in contrast to continued viral shedding that occurs from the gastrointestinal tract for several weeks after clinical recovery.…”
Section: Discussionsupporting
confidence: 62%
“…Although CSF testing is usually positive in enterovirus aseptic meningitis, it is frequently negative in EV71-associated neurological disease, including encephalomyelitis. 3,17,[38][39][40] The present study established that, despite high rates of CNS involvement, EV71 was infrequently identified from CSF specimens, while throat, stool, or rectal swabs had high diagnostic yields. Viral load in the CSF may be low in contrast to continued viral shedding that occurs from the gastrointestinal tract for several weeks after clinical recovery.…”
Section: Discussionsupporting
confidence: 62%
“…2008; Jaramillo‐Gutierrez et al . 2013; Tsai et al 2014). It is important that primers must be frequently reviewed to take into account the rapid evolution and genomic changes of the circulating viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription PCR (RT-PCR) and real-time reverse transcription PCR (qRT-PCR) assays targeting the 5 0 untranslated region (5 0 UTR) are largely used for the diagnosis of enteroviruses (Kottaridi et al 2004;Hymas et al 2008;Jaramillo-Gutierrez et al 2013;Tsai et al 2014). It is important that primers must be frequently reviewed to take into account the rapid evolution and genomic changes of the circulating viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Opsoclonus–myoclonus ataxia syndrome is considered as a rare manifestation of enterovirus 71 across all age groups, even though brain stem symptoms are identified as the most common form of encephalitis caused by this agent. 6,7 As far as the authors know, opsoclonus–myoclonus ataxia syndrome has been reported once in the pediatric literature to be associated with an enterovirus 71 infection, in a 1-year-old girl having favorable outcome. 3 There are limited evidence about the incidence of benign forms of opsoclonus–myoclonus ataxia syndrome.…”
Section: Discussionmentioning
confidence: 99%